Effect of the drying stage of the rice stubble on the weeds and the beans (Phaseolus vulgaris L.). - Herrera Murillo, Franklin; Agüero-Alvarado, Renán (Agronomía Mesoamericana, 2003)
The assay was conducted at the Fabio Baudrit Experiment Station of the University of Costa Rica, located in the San Jose district, in Alajuela, Costa Rica. The effect of drying the rice stubble with glyfosate was measured, between June 2000 and January 2001, in different periods before the direct planting of the beans; on the control of weeds and the bean yield. The application of glyfosate on the rice stubble and weeds, before planting the beans or after planting, but before the emergence, allowed an adequate ground cover by the stubbles during the critical competence period of the bean, which reduced the presence of weeds and achieved high bean yields without applying other herbicides. When the holding period was prolonged (30-45 days) after the glyfosate application, the ground cover was poor due to the advanced decomposing stage of the stubble. There was a larger presence of weeds and negative effects on the bean production when the weed control was not timely.